Desenvolvimento de uma ferramenta computacional para o dimensionamento de sistemas fotovoltaicos isolados e interligados à rede - Pazuch, Félix Augusto (2017)
The present work deals with the development of a computational tool for sizing of photovoltaic systems connected to the network systems of the concessionaire (Grid_tie) and isolated systems (Off_grid). The calculations for the scaling were obtained from the Photovoltaic systems engineering Handbook – CRESESB, technology, design and installation of photovoltaic systems – GREENPO and Digital Book introduction to Solar Systems – BLUESOL. For both systems, the sizing step that resembles the two configurations is the location information of the photovoltaic project. Knowing the data of latitude, longitude and altitude of the site the tool calculates the angle of the modules for better absorption of the photovoltaic radiation. For systems connected to the network, it is also necessary to provide information on the consumption of the building to be serviced by the photovoltaic system. For isolated systems, besides the information of the place, it is necessary to know the demand and consumption of the building. By means of a list of electrical equipment, the equipment dependent on the photovoltaic system is defined. The decisionmaking criteria are based on economic analysis, based on indices such as Net Present Value (NPV), Internal Rate of Return (IRR) and Discounted Payback. As results we presented the screens developed for the sizing tool and examples of sizing of both photovoltaic systems through tables and graphs. The developed application works in an uninterrupted manner without presenting problems and proved to be reliable, since all the calculations are of the sizing algorithm or the calculations of the economic analysis, they have a theoretical basis.